The Relationship Between The Use of Apitherapy Products and The Frequency of Constipation in Adults - Coşkun, Ayfer Beyaz; Turkoglu, Semra; Böler, Ezgi; Tomar, Zehra Betül; Güven, Esra (My University, 2025)
Objective: This study aims to reveal the effectiveness of apitherapy products on constipation, as well as other possible risk factors, in individuals with functional constipation. Material-Method: This cross-sectional study was conducted with 652 adults (460 men and 192 women) between the ages of 18-65 in Turkey. Constipation was defined as defecation frequency of less than 3 times a week. Dietary fluid and fiber intake was assessed by the 62-item food consumption frequency (FFQ). The use of bee products was questioned in terms of quantity and frequency. Physical activity status was questioned with a 3-question short form. Results: It was determined that 17.8% of the cohort (19.1% males, 14.6% females) had constipation. The percentage of constipation was higher in underweight individuals (28.5%) compared to other BMI groups. Individuals with chronic diseases have a higher percentage of constipation (22.4%) than those without the disease. A significant relationship was found between constipation and fiber intake (p = 0.001). Honey (p=0.013) and royal jelly (p=0.030) intake was significantly higher in individuals without constipation than in individuals with constipation. Conclusion: The rate of functional constipation is high in Turkish adults. Fiber intake, presence of chronic disease and BMI affect constipation. Constipation is lower in those who consume honey and royal jelly from bee products. Interventional studies are needed on the use of bee products to reduce the symptoms and frequency of constipation.
Keywords: Fiber; Physical Activity; Constipation; Apitherapy